PENDUGAAN MODEL PARTISIPASI EKONOMI MASYARAKAT PROVINSI JAMBI DENGAN METODE ANALISIS REGRESI LOGISTIK BINER - gusmi kholijah (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2020)
Economic well-being is still uneven in Indonesia. This is still a problem in overcoming poverty. Many efforts have been made in poverty alleviation, one of which is increasing economic participation. Economic participation can be categorized as working and not working. Economic participation is a response variable that is influenced by several predictor variables. The relationship between predictor variables and response variables in the form of binary categories can be analyzed by binary logistic regression. The model generated from this study conveys that people who live in rural areas have more economic participation than those in cities. Then marital status in the category of marriage, divorced life has more economic participation than divorce, and divorced people die more than those who have not yet married. Furthermore, men participate more economically than women. Then when viewed from the age, shows the productive age of work has more economic participation, then the higher the level of education then contributes to the higher economic participation.